Quantitative Interactome Proteomics Reveals a Molecular Basis for ATF6-Dependent Regulation of a Destabilized Amyloidogenic Protein. Issue 7 (18th July 2019) - Plate, Lars; Rius, Bibiana; Nguyen, Bianca; Genereux, Joseph C.; Kelly, Jeffery W.; Wiseman, R. Luke
Summary: Activation of the unfolded protein response (UPR)-associated transcription factor ATF6 has emerged as a promising strategy to reduce the secretion and subsequent toxic aggregation of destabilized, amyloidogenic proteins implicated in systemic amyloid diseases. However, the molecular mechanism by which ATF6 activation reduces the secretion of amyloidogenic proteins remains poorly defined. We employ a quantitative interactomics platform to define how ATF6 activation reduces secretion of a destabilized, amyloidogenic immunoglobulin light chain (LC) associated with light-chain amyloidosis (AL). Using this platform, we show that ATF6 activation increases the targeting of this destabilized LC to a subset of pro-folding ER proteostasis factors that retains the amyloidogenic LC within the ER, preventing its secretion. Our results define a molecular basis for the ATF6-dependent reduction in destabilized LC secretion and highlight the advantage for targeting this UPR-associated transcription factor to reduce secretion of destabilized, amyloidogenic proteins implicated in AL and related systemic amyloid diseases. Graphical Abstract: Highlights: Quantitative proteomics defines the interactome for the amyloidogenic light chain ALLC ATF6 or XBP1s activation distinctly affect interactions between ALLC and ER proteins ATF6 activation reduces ALLC secretion through increased targeting to ER chaperones Enhanced quality control is based on global interaction changes coordinated by ATF6 Abstract : Activating the ATF6 arm of the unfolded protein response selectively reduces the secretion and subsequent toxic aggregation of destabilized amyloidogenic light chains. Plate et al. use a quantitative proteomics platform to identify specific ATF6-regulated ER proteostasis factors responsible for regulating the secretion of an amyloidogenic light chain from mammalian cells.